Hubungan Kewenangan Kepala Sekolah dengan Kinerja Guru - Patar Rumapea (Universitas Negeri Malang, 2016)
This study investigated the influence of principals legitimate power on the teachers performance. It was conducted in ten Public Senior High Schools in Manado. A stratified random sampling was employed in this study to select 140 techers. The data were collected using a questionnaire in the form of statements/questions of Likert scales. The data were then analyzed statistically by descriptive analysis and simple linear regression. The results indicated that the exertion of power by the principal to increase the teachers performance was more of legitimate power, and that the legitimate power influenced the teacherss performance. This finding can be used as a stepping stone to conduct further research on principals legitimate power.